Effect of low-frequency noise on the survival rate and immunity of infected Vibrio parahaemolyticus sea slug (Onchidium reevesii). Issue 126 (July 2022) - Tu, Zhihan; Tang, Liusiqiao; Yang, Hang; Zhang, Xiaoming; Jiang, Chao; Shen, Heding
Abstract: Anthropogenic noise in the marine environment has become a global environmental pollutant that affects the behavior, physiology and immunity of marine animals. However, the resistance of marine animals to pathogens while under the influence of noise is a topic that has received little attention. To assess the immune defense response of sea slugs against pathogens when exposed to low frequency noise, we performed 120 h exposure experiments on sea slugs after a Vibrio parahaemolyticus application in low frequency noise at 500 Hz and 1000 Hz. We found that after the infection with V. parahaemolyticus, the survival rate of the sea slugs decreased, the apoptosis rate and reactive oxygen species (ROS) production of hemocytes increased significantly ( P < 0.05), the proliferation of hemocytes accelerated, the activities of enzymes such as superoxide dismutase (SOD), catalase (CAT), alkaline phosphatase (AKP), alanine transaminase (ALT) and lysozyme (LZM) in the hepatopancreas increased significantly, and the expression of TNF signaling pathway-related genes ( TNF-α, FADD, Caspase 8, Caspase 3 ) and Hsp70 genes were generally upregulated. In addition, exposure of sea slug after infected with V. parahaemolyticus to low frequency noise resulted in a significant increase in both antioxidant and immune parameters, which were positively correlated with frequency. The results showed that noise frequency and exposure time had an interactive effect on the above indicators. In summary, low-frequency noise exposure increases the risk of pathogenic infections in sea slugs and exacerbates the negative effects on the antioxidant capacity and immune metabolism of the organism. Highlights: Low-frequency noise stress increased the susceptibility of sea slug to V. parahaemolyticus infection. The survival of V. parahaemolyticus induced sea slug was lower under exposure to low-frequency noise. The negative effects of low-frequency noise at 1000 Hz on the immune status of sea slug was higher than that at 500 Hz.